Student-Run Teen and Tot Service: Increasing Medical Trainee Exposure to Pediatric Education while Providing Educational and Health Services to Teenage Mothers and their Children - Krumholz, Julia; Mumber, Hannah; Tunstall, Emma; Okaka, Amanda; Nguyen, Minh-Thuy; Webb, Rebecca; Wenren, Larissa; Cournoyer, Eily; Rodriguez, Sarah; Toder, Celine; Pierre-Joseph, Natalie (Journal of Student-Run Clinics, 2022)
Background: Student Run Teen and Tot Service (SRTTS) is a student-run, interdisciplinary service-learning program at Boston University School of Medicine (BUSM) and Boston Medical Center (BMC). In this paper, we describe the program, which aims to increase medical students’ exposure to pediatrics while providing education and support to teenage mothers and their babies. Methods: Medical students at BUSM learned developmental milestones and trained in communication, patient-centered education, and the pediatric interview and physical exam. SRTTS leaders recruited patients to free monthly service evenings held at BMC. The babies received medical exams and the teenage mothers received health and parenting education. Students filled out pre- and post-participation surveys rating their comfort with pediatric medicine and education, and patients completed demographic and satisfaction surveys. Both the patient and student surveys were analyzed using a descriptive approach. Results: Analysis of pre-and post-participation student surveys demonstrated that the mean confidence level (reported on a 5-point scale, with 1=Not at all confident and 5=Extremely confident) increased for all measured domains, including interacting with children and adolescent mothers (from 2.46 to 4.08 and 2.08 to 3.92, respectively), giving anticipatory guidance (from 1.62 to 3.63), and performing a pediatric physical exam (1.08 to 2.85). Patients rated their experience with the program and the care they received highly, indicating that they would use the health education that they received in the future. Conclusions: The supplemental care provided by SRTTS was well received by patients. Additionally, medical students improved their skills in a variety of pediatric medicine and education topics. SRTTS is limited by the number of patients and students who participated. Expanding SRTTS will further integrate adolescent mothers and children into the healthcare system and allow medical students to further increase their proficiency in pediatric medicine.